A Theistic Cosmological Theory Aligned with Principles of Thomism: The Holy Infinite Memory Model of Consciousness - Breslauer, Sam (2024)
This paper presents a classically theistic cosmological model of consciousness that aligns with Thomistic principles. This discussion begins with a focus on the transcendent identity of God the Father existing in eternity, establishing His simple essence as the pure act of being self-conscious, which defines the mind of God as containing a single holy infinite memory; Himself. However, this model suggests His eternal mind also contains a complex infinite collection of unique self-memories all composed of His immutable essence, framed as the origin of differentiated immaterial information. Guided by St Thomas Aquinas' formulation of hylomorphism, creation is understood as the ongoing process of God re-actualizing His self-memories from an immaterial to material form, requiring God to unfold prime matter as His first creation from nothing but His own pre-existent essence. The production of prime matter, as pure potentiality, allows the Father to breathe His Holy Spirit that contains the Word (foreknowledge of all possibilities / information) to manifest creation. This model suggests that formless prime matter can be described as a zero-dimensional point singularity of infinitely dense pure energy that is imbued with the self-consciousness of the Holy Spirit, which extends into a one-dimensional string that can then fragment into different physical entities. The immanent existence of God's holy infinite memory at the incorporeal centre of all created forms further implies that the universe is structured as an unfolding non-local holographic fractal. Formulating the beginning of creation in this way allows us to see possible connections between Christian doctrine, the primacy of information, string theory and other scientific principles that pose new ways in understanding the immaterial nature of the raw fabric of physical reality. Objections against this model, in relation to its alignment with classical theism, are addressed towards the end of this paper. Fundamentally, fresh perspectives are presented on the nature and origin of consciousness that may shed new light in uncovering the persistent deficiencies in our understanding of consciousness itself.
Keywords: Consciousness; DOCTRINAL theology; God; Holy Spirit; Holy Spirit; Memory; THOMAS, Aquinas, Saint, ca. 1225-1274; Thomism; Thomism; Consciousness; Energy; Essence; holographic fractal; Information; Memory; strings